Iron overload correlates with serum liver fibrotic markers and liver dysfunction: Potential new methods to predict iron overload-related liver fibrosis in thalassemia patients. Issue 1 (February 2017) - Wang, Man; Liu, Rongrong; Liang, Yuzhen; Yang, Gaohui; Huang, Yumei; Yu, Chunlan; Sun, Kaiqi; Lai, Yongrong; Xia, Yang
Background: Early detection of liver fibrosis in thalassemia patients and rapid initiation of treatment to interfere with its progression are extremely important. Objective: This study aimed to find a sensitive, easy-to-detect and noninvasive method other than liver biopsy for early detection of liver fibrosis in thalassemia patients. Methods: A total of 244 Chinese Thalassemia patients with non-transfusion-dependent thalassemia (NTDT, n = 105) or thalassemia major (TM, n = 139) and 120 healthy individuals were recruited into the present study, and blood collagen type IV (C IV), precollagen type III (PIIINPC) and hyaluronic acid (HA), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and ferritin were measured. Liver iron concentration was determined by MRI. The correlation of serum markers with liver iron load and liver function was evaluated. Results: Serum C IV, PIIINPC and HA were significantly elevated in Chinese patients with NTDT and further elevated in TM patients. Moreover, C IV, PIIINPC and HA were also positively correlated to serum ferritin and liver iron concentration and further elevated during the progression to multi-organ damage in NTDT patients. Finally, serum ferritin and liver iron concentration were significantly correlated with liver dysfunction determined by AST and ALT. Conclusion: Taken together, our results indicate that monitoring serum C IV, PIIINPC and HA is a potentially sensitive method to predict the risks for iron overload-related liver fibrosis in Chinese thalassemia patients.